Integrated taxonomy of a new species of black fly in the subgenus Trichodagmia (Diptera: Simuliidae) from the Páramo Region of Colombia - Diaz, Sofia A.; Moncada, Ligia I.; Murcia, Carlos H.; Lotta, Ingrid A.; Matta, Nubia E.; Adler, Peter H. (Zootaxa, 2015)
A new species of simuliid from the Andean Mountains of Colombia is described on the basis of females, males, pupae, larvae, polytene chromosomes, and COI and ITS2 DNA sequences. Simulium (Trichodagmia) chimguazaense new species is structurally, chromosomally, and molecularly distinct from its nearest relatives, S. muiscorum Bueno, Moncada & Muñoz de Hoyos and S. sumapazense Coscarón & Py-Daniel.